Assessing alternative assessment for psychomotor domain in engineering education: insights from a qualitative case study analysis / Nur Asmaliza Mohd Nor ... [et al.] - Mohd Nor, Nur Asmaliza; Oh, Chai Lian; Tahir, Wardah; Tukiar, Mohd Azuan; Mat Isa, Che Maznah (Universiti Teknologi MARA, Perlis, 2025)
The psychomotor domain of learning outcomes is required to equip the engineering graduate with the necessary attributes and skills. The measurement of psychomotor domain learning outcome is not straightforward compared to the cognitive domain of learning, which generally uses examination and tests to assess students’ performance. The COVID-19 pandemic has posed a more significant challenge to assessment activities, and alternative remote assessment and teaching activities have been introduced since fieldwork and actual laboratory setups have been inaccessible. This paper evaluates the effectiveness of various implementations of course assessment under the psychomotor domain of learning for a civil engineering degree programme offered at Universiti Teknologi MARA Pulau Pinang. The efficacy of these alternative assessments in delivering the intended learning outcomes needs to be analysed for continual quality improvement (CQI). This study employed a qualitative case study approach, utilizing document analysis of the revised curriculum, syllabus for ODL, sample assessments, and related materials to examine the implementation of remote assessments in evaluating students' psychomotor skills. The findings indicate that the evaluated alternative remote assessments hardly assess the true attainment of student engineering practices and specialist knowledge in laboratory conduct during the pandemic. Despite various alternative assessments being identified, most can only develop student psychomotor skills up to level P2 (i.e. awareness). This study offers valuable insights for CQI, aiding in the enhancement of curriculum design to ensure alignment with the psychomotor learning outcomes essential for engineering education.